ζ-Open Sets and ζ-Continuity - Sabah A. Tamer; Taha H. Jasim (Tikrit Journal of Pure Science, 2023)
In this work, the concept of ζ-Open Set was introduced as a generalization of open set. Where it is shown that (X, ) is a Topological Space.